*-Lie-type maps on C*-algebras. Issue 12 (2nd December 2022) - Nascimento Ferreira, Ruth; Macedo Ferreira, Bruno Leonardo; Guzzo Junior, Henrique; Costa, Bruno Tadeu
Abstract: Let A and A ′ be two C * -algebras with identities I A   and I A   ′, respectively, and P 1 and P 2 = I A   − P 1 nontrivial symmetric projections in A . In this paper, we study the characterization of multiplicative * -Lie-type maps. In particular, if M is a factor von Neumann algebra then every complex scalar multiplication bijective unital multiplicative * -Lie-type map is * -isomorphism.